ANALISIS TATA LAKSANA FRAKTUR DISTAL RADIUS DAN OS SKAFOID PERGELANGAN TANGAN PADA POPULASI AKTIF - Rahman Muhammad Hasan; Muhammad Rafi Zulfikar; Dafa Wishnu Moerara; Muhammad Arief Setiawan; Miftahudin Sigit Miftahudin Sigit (Fakultas Ilmu Keolahragaan Unimed, 2026)
Wrist fractures, particularly Distal Radius Fracture (DRF) and Scaphoid Fracture, are common musculoskeletal injuries among active populations, such as athletes. DRF often occurs due to a fall on an outstretched hand (FOOSH), while scaphoid fractures have a high risk of complications, including non-union and avascular necrosis (AVN). This study aims to analyze the injury mechanisms, diagnostic accuracy, and the comparison between conservative and operative management of wrist fractures. A systematic literature review was conducted, focusing on studies from 2018 to 2025. The results indicate that internal fixation with a volar locking plate for unstable DRF provides better functional outcomes compared to conservative treatment. Meanwhile, displaced scaphoid fractures require percutaneous screw fixation to achieve optimal healing. In conclusion, individualized treatment is crucial, with minimally invasive surgical intervention being the preferred approach for complex fractures. Keywords: Distal Radius Fracture, Scaphoid Fracture, Wrist Injury, Operative Management, Volar Locking Plate.